Long-term Perspective in Coastal Zone Development Multifunctional Coastal Protection Zones - Ahlhorn, Frank (Springer Berlin Heidelberg : Imprint: Springer, 2009)
From February 2004 until December 2007 the ComCoast project (Combined Fu- tions in Coastal Defence Zones) was carried out within the Interreg IIIB framework. The objective of this project was to investigate and to test the options for spatial coastal protection concepts. The mission statement of the project over its entire duration was: A wider approach in coastal thinking. I was glad to be part of this project and would like to thank all my European colleagues for the constructive and cooperative atmosphere. Firstly, I would like to express my thanks to Prof. Dr. Horst Sterr and Prof. Dr. Hans Kunz who assisted me over these years with their thorough guidance and comprehensive expertise and for many in-depth discussions on the focus of this dissertation. Secondly, I would like to thank my colleague Dr. Jur ¨ gen Meyerdirks, who acted as my key scienti c sparring partner over the last two years, and who continuously demonstrated his ability to bring me back to earth. Additionally, I would like to thank my colleague Dr. Thomas Klenke, who gave me the chance to be part of a challenging European project consortium and who supported me with his expertise on the project and the dissertation. Furthermore, I would like to express my special thanks to Gerard McGovern, who thoroughly improved my English.